High-performance polyimide fiber by low-temperature thermal imidization from polyamic acid precursor fiber via dry-jet wet-spinning - Jian Zhao; Xun Meng; Hongwei Piao; Hao Zhang; Zhibo Ren; Qi Han; Qinglin Huang; Hanli Wang (eXPRESS Polymer Letters, 2025)
Polyimide (PI) fiber is a promising and high-performance polymer fiber with high temperature resistance and low density; however, much energy is needed during the thermal imidization process. Here, PI fiber with excellent mechanical properties and high-temperature resistance was fabricated via the dry-jet wet spinning method for polyamic acid (PAA) precursor fiber, followed by stretching and thermal imidization reaction at a lower temperature. With the increase of the stretching ratio, the mechanical properties of the PI fiber increase significantly. When the stretching was twice as long, the tensile strength and initial modulus of the fiber were as high as 6.23 and 114.13 cN·dtex–1, respectively. Fourier transform infrared results revealed that all samples were completely imidized at 260 °C. The resulting PI fibers exhibit only 5% weight loss at 539.53 °C, and its limiting oxygen index (LOI) can reach up to 32.6%, showing excellent high temperature resistance and flame-retardant properties as well as commendable mechanical performance, which compare favorably with those of other imidization methods.